Religion and Identity – Anthropological Guiding Lines - BUZALIC, Alexandru (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2020)
The human being is homo religiosus through his ability to experience the sacred, laying special emphasis on the meaning of existence of all things, expressed afterwards in a metaphysical interpretation concealed behind symbolic-religious language. One of the most important processes of integration into reality is self-identification as a person and gaining a group identity –processes that take different shapes over the history of human existence. The formation of state entities has always been preceded by a process of creating a social identity that manifests itself through the spiritual life materialized in culture and religion. These processes have led to the birth of mediaeval states and then to the shaping of modern Europe, necessary to the deconstructions and reconstructions in the inter-war time. These processes are also visible today during cultural globalization. What we need is a critical approach on unity in diversity that characterizes humanity in history and that will shape the future evolution of humanity.